The NMR-measured omega-6/omega-3 fatty acid ratio improves cardiovascular risk prediction - Huang, Youwei; Lu, Xianzhou; Shen, Yanyan; Liu, Ying; Zeng, Qiqing; Liu, Xianrong; Bin, Wenkai; Li, Meili (Frontiers in Nutrition, 2025)
BackgroundImproving 10-year cardiovascular risk prediction beyond the established SCORE2 algorithm is a clinical need. The plasma omega-6/omega-3 (O6:O3) polyunsaturated fatty acid (PUFA) ratio, a marker of inflammatory balance, is a promising biomarker for enhancing risk stratification. We aimed to evaluate if adding the O6:O3 ratio to the SCORE2 model improves the prediction of major adverse cardiovascular events (MACE).MethodsWe conducted a prospective cohort study of 183,230 UK Biobank participants (aged 50–69 years, free of baseline cardiovascular disease or diabetes). The plasma O6:O3 ratio was measured by nuclear magnetic resonance (NMR) spectroscopy. We compared the predictive performance of the SCORE2 model with and without the O6:O3 ratio in an independent validation cohort (N = 54,940) using Harrell’s C-index, Net Reclassification Improvement (NRI), and Integrated Discrimination Improvement (IDI).ResultsIn the validation set, adding the O6:O3 ratio to SCORE2 significantly increased the C-index from 0.742 (95% CI: 0.738–0.746) to 0.747 (95% CI: 0.743–0.751) (p < 0.001). The extended model also significantly improved risk reclassification (NRI 8.4, 95% CI: 3.6–12.2%; IDI 0.021, 95% CI: 0.010–0.032). This improvement was more pronounced in men than in women, and both models remained well-calibrated.ConclusionIncorporating the plasma O6:O3 PUFA ratio provides a modest but statistically significant improvement in 10-year MACE risk prediction with the SCORE2 algorithm. As a modifiable biomarker, the O6:O3 ratio holds potential to refine risk stratification and guide personalized nutritional interventions.